Evaluation of user satisfaction on hospital information system: a Malaysian case study / Lidyawati Abdul Hamid - Abdul Hamid, Lidyawati (2016)
The advancement of the Hospital Information System in Malaysia begun with a fundamental factual reporting framework utilizing papers to an ICT based Hospital Information System. Hospital Information System (HIS) which has been executed and utilized subsequent to 1998. HIS is an integration of clinical, administrative and financial module developed by the Ministry of Health, Malaysia, to deliver health care services through information technology and a combination of terrestrial lines and satellite communication channels. Hospital Information System is a tool to help in enhancing the quality of care and to provide continuous and seamless care in hospitals, by bringing physician closer to patients. Care providers will be able to access patient's electronic medical records whenever they are in the vicinity of clinics or hospitals. However, not every hospital in Malaysia is using it. Some of the problems are lack of acceptance and under-utilized by the users, users reluctant to gain knowledge of new methods, Negative impacts on the clinician-patient relationship and Development Hospital Information System is not consistent. Thus, more investigation and studies needed to be conducted in order to determine the system in verifying the resume of maintaining the quality of the system and specialist cares' satisfactions. The main objective of this experimental research is to investigate the user satisfaction by difference users and to identify the significant factors for user satisfaction in using Hospital Information System in public hospitals. This research uses quantitative research method and adapted the DeLone and McLean Information Systems Success Model (D&M IS Success Model). The main target group was the end users (doctor, nurses, pharmacists and others) instead of the developer and service managers. In order to confirm the level of customer satisfaction and different satisfaction level among different position of users, data gathered will be analysed by using SPSS software. The data will be assessed with Kruskal-Wallis H test technique. In addition, the result will ' be compared with existing evaluation studies and recommendation being made to improve HIS in the future. Analysis by Kruskal-Wallis H test is proves that statements are 'Medical Record Officer' had the highest satisfaction across eight groups' users. Samples consist of 124 respondents from 5 hospital such as Sedang Hospital, Sg. Buloh Hospital, Sultan Abdul Halim Hospital, Kepala Batas Hospital and Lahad Datu Hospital where there use the same Hospital Information System version 5.x which in develop by the same vendor. The data was gathered through collection online survey.